Ex situ conservation of the endangered “sempre-viva” species Comanthera mucugensis (Acta Scientiarum. Biological Sciences, 2022)
The “sempre-viva” species Comanthera mucugensis is endemic to the municipality of Mucugê, Bahia, Brazil, where it was widely exploited through extractivism to be commercialized as an ornamental, causing a drastic reduction of its population, so that it is now classified as endangered. Although its main area of occurrence is now protected for being within Chapada Diamantina National Park, the continued risks of inclement conditions and anthropic actions make it necessary to develop alternative methods for ex situ conservation of the species, such as in vitro conservation. Therefore, the objective of this study was to test the effect of different concentrations of salts and sucrose on the in vitro conservation of Comanthera mucugensis. Two salts concentrations of the medium MS (½ and ¼) and two sucrose levels (7.5 and 15.0 g L-1) were tested, and the experimental design was completely randomized with four treatments. After 365 days, the survival, growth and regeneration of the conserved plants were analyzed, achieving up to 100% survival, reduced shoot growth and maintenance of regenerative capacity. Reduction of the concentration of salts and sucrose in the culture medium is indicated to conserve the plants in vitro for a period of one year.